Bibliometric Analysis of Studies Related to Undergraduate Nursing Students Indexed in the Web of Science Core Collection Database - Fatma Dursun Ergezen; Ayla Kaya (Global Nursing Insights, 2026)
Aim: This study aims to conduct a comprehensive bibliometric analysis of studies related to undergraduate nursing students indexed in the Web of Science Core Collection (WoSCC) database. Materials and Methods: This descriptive bibliometric study was conducted using data retrieved from the WoSCC. A topic-based search strategy was applied using Medical Subject Headings (MeSH) and relevant keywords related to undergraduate nursing students. Only peer-reviewed, English-language articles and review papers were included. Bibliometric analyses such as thematic mapping, thematic evolution, and keyword co-occurrence analysis were performed using the Bibliometrix package in R. Results: In this study, 3,405 author keywords were analyzed. The co-occurrence analysis revealed three clusters: nursing student, nursing education, simulation, and clinical practice or placement; knowledge and attitude; and stress, anxiety, mental health, and COVID-19. In the thematic map, clinical practice and clinical placement were identified as motor themes, while stress and anxiety were classified as emerging or declining themes. Trend topic analysis showed that earlier periods focused on topics such as clinical practice, simulation, and curriculum, whereas after 2020, issues such as anxiety, stress, and resilience became more prominent. The thematic evolution analysis indicated that the research focus has clearly expanded toward clinical competence, mental health, and pedagogical quality. Conclusions: The findings indicate that clinical practice and simulation are central themes in the studies. Over time, the focus of this literature has expanded beyond traditional educational and clinical frameworks to increasingly encompass students’ psychosocial experiences and global health crises. Implications for nursing practice: In nursing education, there is a need to strengthen practices that support students’ mental health and resilience in addition to developing clinical competencies. It is important for educational and health policies to integrate clinical training processes with psychosocial support and equity-oriented approaches.